Comparative study on combustion and emission characteristics of methanol, ethanol and butanol fuel in TISI engine. (1st January 2020) - Tian, Zhi; Zhen, Xudong; Wang, Yang; Liu, Daming; Li, Xiaoyan
Highlights: The performances of methanol, ethanol and butanol in SI engine were compared and analyzed. The methanol-gasoline blends can better improve the BP and BTE of the engine. The butanol-gasoline blends have the lowest HC emissions and BSFC. The overall effect of ethanol on the engine is between methanol and butanol. Abstract: At present, methanol, ethanol and butanol are recognized clean fuels and have been extensively studied. This paper mainly studies the combustion and emission characteristics of methanol, ethanol and butanol blended with gasoline under different engine speed, load, flame kernel radius and ignition time. The results show that adding alcohol fuels to gasoline can increase the brake torque (BT) and heat release rate (HRR) of the engine. Moreover, the ability of methanol to increase BT and HRR is higher than that of ethanol and butanol, and the increase effect of butanol is the worst. In terms of fuel economy, the addition of alcohol fuels to gasoline can increase the brake thermal efficiency (BTE) of the engine, but brake specific fuel consumption (BSFC) is also increased. Compared with ethanol and butanol, methanol can better increase BTE of the engine, but it also increases BSFC even more. In terms of emissions, the addition of alcohol fuels to gasoline can reduce CO and CO2 emissions, but HC emissions are increased. Under certain conditions, M20 combined with ignition time can better reduce NOx emissions. In general, the addition of alcohol fuels to gasoline while adjusting the ignition time and flame kernel radius can effectively improve engine torque and reduce fuel consumption and exhaust emissions.